"They were the ones that saw me and listened." From child sexual abuse to disclosure: Adults' recalls of the process towards final disclosure. (March 2019) - Brattfjell, Maria Larsen; Flåm, Anna Margrete
Abstract: Background: When child sexual abuse (CSA) is not disclosed, children run the risk of being subjected to longer or repeated abuse, not receiving necessary treatment, and being re-victimized. Objective: This study examines what adults exposed to child sexual abuse in hindsight evaluate as important for disclosure. The aim was to explore exposed own experiences of steps towards final disclosure. Participants and setting: Data were obtained from adult users of Norwegian Sexual Abuse Support Centers. Included were users exposed to CSA before the age of 18 (N=23). Methods: Data were collected through anonymous questionnaires at each support center. The material was transcribed and analyzed in the tradition of Interpretative Phenomenological Analysis. Results: The study illustrates a process towards disclosure as a dialogically anchored process evolving over time and along life-course inside encounters with important others towards whom the exposed pays attention, attunement, and adjustment whether to tell, delay, re-try, turn towards others, or actually disclose. Their experiences elucidate processes towards exploring and telling through direct and indirect hints and signs, decisions to tell, re-decisions and delaying, or withholding until adulthood, and the dependency on trusted confidants who ask and listen for final disclosure to occur. Conclusion: Thus, the present study sends an important message to exposed, confidants, and professionals when questions of CSA appear. That is to know of, facilitate, trust, and tolerate the dialogical dependency on being asked and heard by trusted persons and the many steps a process towards disclosure of CSA may entail in order to succeed.